2011
DOI: 10.1007/s11469-011-9322-9
|View full text |Cite
|
Sign up to set email alerts
|

Why is Childhood Maltreatment Associated with Adolescent Substance Abuse? A Critical Review of Explanatory Models

Abstract: Childhood maltreatment and adolescent substance abuse are important health issues that have been linked by research and theory for at least 50 years. Considering the intricacies of child maltreatment research, this paper aims to answer the question: which models show the most promise to explain why child maltreatment is a risk indicator for adolescent substance abuse? Models of the mechanisms of this association are reviewed and evaluated in the context of the many complexities of defining and measuring child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 92 publications
1
26
0
Order By: Relevance
“…Perhaps this pattern of functioning is not far from the experience of some adolescents dealing with peers, by whom they want to be accepted. The perception of a possible rejection from others may increase difficulties in knowing what they are feeling, to think clearly about it and to behave properly, in a way that these dysfunctional skills of emotional self-regulation may contribute to rejection by mainstream peers (Hovdestad et al 2011). In the presence of anxiety, but also self-derogation feelings (Taylor et al 2005), the contact with some substances may be viewed by some individuals as a form to decrease their social distress, as Gross and Thompson pointed out (2007), which highlights the role of the negative affect for increasing the difficulties to regulate emotions and rejection thoughts and feelings, both particularly relevant for establishing contact with psychoactive substances.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps this pattern of functioning is not far from the experience of some adolescents dealing with peers, by whom they want to be accepted. The perception of a possible rejection from others may increase difficulties in knowing what they are feeling, to think clearly about it and to behave properly, in a way that these dysfunctional skills of emotional self-regulation may contribute to rejection by mainstream peers (Hovdestad et al 2011). In the presence of anxiety, but also self-derogation feelings (Taylor et al 2005), the contact with some substances may be viewed by some individuals as a form to decrease their social distress, as Gross and Thompson pointed out (2007), which highlights the role of the negative affect for increasing the difficulties to regulate emotions and rejection thoughts and feelings, both particularly relevant for establishing contact with psychoactive substances.…”
Section: Discussionmentioning
confidence: 99%
“…In a provincewide survey, Walsh et al (2003) found that the likelihood of experiencing sexual or physical abuse in childhood increased with parental substance abuse. Substance-abusing caregivers may also struggle with psychosocial and financial difficulties and their substance abuse can expose the infant to other adversities because of a lack of supervision or exposure to negative modeling (Hovdestad et al 2011;Takayama et al 1998;Tonmyr et al 2010b). …”
Section: Discussionmentioning
confidence: 99%
“…However, while a link between child maltreatment and substance abuse appears clear, several pathways may underlie that link. Hovdestad et al (2011) reviewed potential explanations of the link between child maltreatment and adolescent substance abuse. These authors suggested that three types of models have been proposed: 1) PTSD models that emphasize the role of trauma in increasing substance abuse, 2) models that emphasize the role of substance use in relieving negative affect produced by self-dysfunction caused by maltreatment, and 3) models that focus on disruptions in relationships, produced by maltreatment, as causes for later substance abuse.…”
Section: The Link Between Child Maltreatment and Substance Abusementioning
confidence: 99%